PHYSICAL QUALITY EVALUATION AND ANTIOXIDANT ACTIVITY OF RED WATERMELON (Citrullus lanatus Thunb.) RIND EXTRACT LOTION - Purwasih, Ratih; Nasikin, M. Ali (Jurnal Jamu Kusuma, 2023)
Skin is an organ that covers the entire surface of a living creatures’s body. The topical preparations such as lotions is widely used to protect the skin from free radicals because the antioxidant content. One of plant that can be used is watermelon. Red watermelon rind contains lycopene, vitamin C, niacin, citrulline, beta-carotene, and vitamin E, which function as antioxidants. The aim of this study was to determine the physical quality and antioxidant activity of red watermelon rind extract lotion (Citrullus lanatus Thunb.). This methods of research was a quantitative descriptive. The lotion was made in four formula with various concentration of extract including F0(0%), F1(5%), F2(10%), and F3(20%). The lotion was evaluated for physical quality and antioxidant activity using a UV-Vis spectrophotometer. Physical quality assay for lotions include organoleptic, homogeneity, spreadability, stickiness, pH, and viscosity assay. The result of organoleptic F0 was a white in color, semi-solid, and has a distinctive base smell. The F1-F3 lotion was brownish-white, semi-solid, and has a characteristic smell of watermelon rind. The lotions were homogeneous, with spreadibility of 5.23-6.35 cm, stickiness of 1.55-3.50 seconds, pH of 5.50-6.81, and viscosity of 2755-4351 cps. The lotion F0 was classified as very weak antioxidant activity with an IC50  of 577.59 ppm, F1-F2 were classified as the moderate antioxidant activity with IC50 of 141.91 ppm and 100.31 ppm, and F3 was a strong antioxidant activity with IC50 of 59.93 ppm. All lotion formulas have complied with the topical preparation reference and SNI-16-4399-1996.